On the origins of life - Miller Jr., William B. (Henry Stewart Talks, 2016)
The Origin of Life, Physics entrained, Multiple theories over the ages, Character and origination of organic molecules linking to self organization, Necessity of cells, Theoretical pathways to the origination of life, Exploration of what actually constitutes life, Emphasizes the paramount aspects of cognition, communication, and cellular collaboration towards problem solving in evolution